Social Exclusion in Later Life
XXIX, 450 p. 28 illus.
Keywords: Drawing on interdisciplinary, cross-national perspectives, this open access book contributes to the development of a coherent scientific discourse on social exclusion of older people. The book considers five domains of exclusion (services; economic; social relations; civic and socio-cultural; and community and spatial domains), with three chapters dedicated to analysing different dimensions of each exclusion domain. The book also examines the interrelationships between different forms of exclusion, and how outcomes and processes of different kinds of exclusion can be related to one another. In doing so, major cross-cutting themes, such as rights and identity, inclusive service infrastructures, and displacement of marginalised older adult groups, are considered. Finally, in a series of chapters written by international policy stakeholders and policy researchers, the book analyses key policies relevant to social exclusion and older people, including debates linked to sustainable development, EU policy and social rights, welfare and pensions systems, and planning and development. The book’s approach helps to illuminate the comprehensive multidimensionality of social exclusion, and provides insight into the relative nature of disadvantage in later life. With 77 contributors working across 28 nations, the book presents a forward-looking research agenda for social exclusion amongst older people, and will be an important resource for students, researchers and policy stakeholders working on ageing.